(untitled) (Revista de Estudos da Linguagem, 2005)
Considering urgent the demand for the construction oflinguistically-motivated lexicons for Natural Language Processingsystems, this paper presents a linguistic-computationalrepresentation for the Brazilian Portuguese adjectives that projecta valence. In order to propose this representation, the microstructureof the mental lexicon and the conception of lexical item areinvestigated from a (psycho)linguistic perspective. In addition,(i) the main properties of the valence adjectives are describedand (ii) some of the main lexical-grammatical representationformalisms are investigated. Finally, a lexical entry template forthese adjectives based on the features structures or attributevaluematrix formalism is proposed.